A re-assessment of Taxomyces andreanae, the alleged taxol-producing fungus, using comparative genomics - Tian Cheng; Miroslav Kolařík; Luis Quijada; Marc Stadler (IMA Fungus)
Abstract The monotypic “bulbilliferous hyphomycete” genus Taxomyces was erected in 1993 for a fungal endophyte isolated from the Yew tree Taxus brevifolia and named Taxomyces andreanae. This fungus was reported to produce the plant-derived anti-cancer drug taxol. The original description of the fungus was not conclusive as to its taxonomic position because no sporulation or other salient morphological features were reported. Consequently, the taxonomic affinities of this fungus have remained obscure. However, a full genome sequence of this strain was generated by a German research group in 2013, in an unsuccessful attempt to detect the biosynthesis genes encoding for taxol. This prompted us to search for phylogenetic marker genes and compare those with the data that recently have become available from state-of-the-art polyphasic taxonomic studies. Surprisingly, the strain turned out to belong to the phlebioid clade of wood-destroying Basidiomycota as inferred from a comparison of its partial ITS, the 28S rDNA (LSU), the RNA polymerase II largest subunit (rpb1), the RNA polymerase II second largest subunit (rpb2), and the translation elongation factor 1-α (tef1) sequences. A multi gene genealogy based on these loci revealed that the closest relative is Ceriporiopsis (syn. Mycoacia) gilvescens. Even though such wood-destroying Basidiomycota are regularly encountered among the endophytic isolates after surface-disinfection of plant organs, the vast majority of the reported endophytic fungi belong to the Ascomycota. Nevertheless, the data available now allow for synonymizing Taxomyces with Ceriporiopsis, and the necessary new combination is made.